2005
DOI: 10.1021/bi050327i
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitric Oxide in Amyloid Fibril Formation on Transthyretin-Related Amyloidosis

Abstract: Although oxidative stress is said to play an important role in the amyloid formation mechanism in several types of amyloidosis, few details about this role have been described. Amyloid is commonly deposited around the vessels that are the primary site of action of nitric oxide generated from endothelial cells and smooth muscle cells, so nitric oxide may be also implicated in amyloid formation. For this study, we examined the in vitro effect of S-nitrosylation on amyloid formation induced by wild-type transthyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…15,[42][43][44][45] We previously reported evidence of oxidative stress in deposits of amyloid in tissues of patients with FAP. 45 Our more recent in vitro studies also showed that nitric oxide-mediated modification of TTR may have an important role in amyloid formation.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…15,[42][43][44][45] We previously reported evidence of oxidative stress in deposits of amyloid in tissues of patients with FAP. 45 Our more recent in vitro studies also showed that nitric oxide-mediated modification of TTR may have an important role in amyloid formation.…”
Section: Discussionmentioning
confidence: 98%
“…15,22 Albumin was isolated from serum samples from healthy volunteers by means of ion-exchange chromatography. Albumin-containing bound fatty acids (FA-albumin) was donated by the Chemo-Sero-Therapeutic Research Institute (Kaketsuken, Kumamoto, Japan) and was isolated by using a Sephadex G-25 column (Nihon Waters K.K., Tokyo, Japan).…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
See 3 more Smart Citations